IMPROVEMENT OF SOME SOIL CHEMICAL PROPERTIES ON MARGINAL LANDS TO INCREASE CORN PRODUCTION THROUGH CONSERVATION TILLAGE TECHNIQUES AND ORGANIC FERTILIZERS - Kusairi, David; Sunarti; Aswandi (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
This study aims to analyze the effect of applying conservation tillage techniques and a combination of organic and inorganic fertilizers on soil chemical properties on marginal land and maize production. This research was conducted in Jambi Outer City District, Muaro Jambi Regency, Jambi Province, from January to April 2021 using a randomized block design with 15 treatments and 3 replications. Parameters observed were corn plant height at the age of 15 DAP, 30 DAP and 45 DAP, weight of corn cobs, weight of dry shelled corn seeds, Soil pH, Soil C-Organic Content, Soil Nitrogen Content, Soil Phosphorus Content, Soil Potassium Content, Cation Exchange Capacity, Base Saturation. The results showed that the application of conservation tillage techniques and a combination of organic and inorganic fertilizers had a significant effect on corn plant height 45 DAP, corn cob weight, soil pH, C-Organic Soil, Soil Phosphorus Content, Soil Potassium Content, Cation Exchange Capacity.